Sheek Yusuf Al-Makassari's Thoughts on Implementation of Islamic Law Through India - Muhamad Mas’ud; Fadllurrrohman Fadllurrrohman (Green Publisher Indonesia, 2022)
This research is a case study on the thoughts of Sheikh Yusuf al-Makasari. This study aims to analyze the thoughts of Sheikh Yusuf al-Makasari about the application of Islamic law and its application through the judicial institutions of the Dutch East Indies colonial period. This study uses qualitative methods which include library research studies, namely reviewing literature related to Sheikh Yusuf and studies relevant to Sheikh Yusuf. The results of this study are that Sheikh Yusuf's accommodationist attitude vis-a-vis the Netherlands is solely in order to prevent political disturbances and disturbances that harm society and maintain the continuity of Islamic law as desired in the political understanding of the Ahl al-Sunnah wa al-Jama'ah; In his efforts to implement Islamic law effectively in the archipelago, this Betawi cleric has also succeeded in compiling Islamic family law materials (marriage, divorce, and inheritance).